2013
DOI: 10.1002/etc.2121
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐tolerance in amphibians: Wood frog mortality when exposed to three insecticides with a common mode of action

Abstract: Abstract-Insecticide tolerance and cross-tolerance in nontarget organisms is often overlooked despite its potential to buffer natural systems from anthropogenic influence. We exposed wood frog tadpoles from 15 populations to three acetylcholine esterase-inhibiting insecticides and found widespread variation in insecticide tolerance and evidence for cross-tolerance to these insecticides. Our results demonstrate that amphibian populations with tolerance to one pesticide may be tolerant to many other pesticides. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…For example, Bridges and Semlitsch (2000) demonstrated that populations of leopard frogs (Lithobates sphenocephalus) vary in their tolerance to the insecticide carbaryl. Similarly, Cothran et al (2013) and Hua et al (2013a) found that populations of wood frogs (Lithobates sylvaticus) vary substantially in their tolerance to the insecticides chlorpyrifos, carbaryl, and malathion. Further, consistent with predictions of evolved tolerance, Bendis and Relyea (2014) and Cothran et al (2013) demonstrated that populations of waterfleas (Daphnia pulex) and wood frogs living farther from agriculture were less tolerant to a single, commonly applied insecticide (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…For example, Bridges and Semlitsch (2000) demonstrated that populations of leopard frogs (Lithobates sphenocephalus) vary in their tolerance to the insecticide carbaryl. Similarly, Cothran et al (2013) and Hua et al (2013a) found that populations of wood frogs (Lithobates sylvaticus) vary substantially in their tolerance to the insecticides chlorpyrifos, carbaryl, and malathion. Further, consistent with predictions of evolved tolerance, Bendis and Relyea (2014) and Cothran et al (2013) demonstrated that populations of waterfleas (Daphnia pulex) and wood frogs living farther from agriculture were less tolerant to a single, commonly applied insecticide (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…Over the last several years, we have used wood frogs ( Lithobates sylvaticus ) to explore patterns in pesticide tolerance (Hua, Cothran, Stoler, & Relyea, 2013; Hua, Jones, & Relyea, 2014; Hua et al., 2015). Wood frog populations inhabit pond ecosystems that can encounter pesticides following direct application, runoff, or aerial drift (Smalling et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wood frog populations inhabit pond ecosystems that can encounter pesticides following direct application, runoff, or aerial drift (Smalling et al., 2015). Using 15 populations in northwestern Pennsylvania (Hua et al., 2013, 2014, 2015), we found that populations living close to agriculture have higher baseline tolerance to a common acetylcholineesterase (AChE) inhibiting pesticide (carbaryl) compared to populations living far from agriculture (Hua et al., 2015). Using the same populations, we also investigated patterns of plasticity to carbaryl and found that the degree of plasticity to carbaryl varied along an agricultural gradient; populations close to agriculture possess high baseline but no inducible tolerance to carbaryl (i.e., constitutive tolerance), whereas populations far from agriculture possess low baseline but high inducible tolerance to carbaryl (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two types of pyrethroids cause toxicity through similar modulations of the voltage-gated sodium channels, but the degree of modification of sodium currents is different; single sodium channel currents are prolonged to a greater extent with type-II than type-I pyrethroids (Clark and Matsumura 1982;Nasuti et al 2003;Wouters and van den Bercken 1978). Organophosphates (e.g., chlorpyrifos) inhibit acetylcholine esterase activity (Hua et al 2013;Malison et al 2010) directly impacting the synaptic signal. Varying modes of action could thus drive various exposure effects among different test endpoints.…”
Section: Introductionmentioning
confidence: 99%